Perenniporia punctata sp. nov. (Polyporales, Basidiomycota), a new species discovered from China - Li, Hai-Jiao; Zhou, Meng; Si, Jing (Phytotaxa, 2018)
Taxonomic and phylogenetic studies on Perenniporia were carried out. Phylogeny based on ITS and nrLSU regions revealed that a species clustered within the Perenniporia s.s. clade, further morphological study showed three specimens collected from Hubei Province, central China represent an undescribed species. In the present study, Perenniporia punctata sp. nov. is described. It is characterized by its perennial, resupinate basidiocarps, small circular pores (6–9 per mm) with colour of cream, buff-yellow to pale yellow which turned to clay-buff to cinnamon when bruised, distinctly stratified tubes, a dimitic hyphal system with slightly dextrinoid, cyanophilous skeletal hyphae, and broadly ellipsoid to subglobose, truncate, hyaline, thick-walled, smooth, IKI–, strongly cyanophilous basidiospores (5.5–7 × 4–6 µm).